(untitled) (Research, Society and Development, 2020)
Angle Class II is one of the malocclusions most sought for treatment and a great challenge for the orthodontists. When patients present a mandibular deficiency still in the growth phase, functional appliances are usually chosen to correct this problem. However, in some situations, the lack of patient cooperation in using these appliances, especially removable ones, may compromise the result of the orthodontic treatment. Considering the evolution of mandibular propellers, several function models started to appear in the market, and among them is the PowerScope - a fixed hybrid propeller. Nevertheless, one of the effects expected from all propellers, either removable or fixed ones, besides dentoalveolar remodeling, is an excessive labial inclination of lower incisors. Thus, this study aimed to show the use of the PowerScope II for correcting Angle Class II in a 12-year-old patient with mandibular deficiency, brachyfacial, and with proclination of upper and lower incisors. After detailed planning, a 0.022" Roth prescription fixed appliance was selected, followed by the PowerScope II and lower bilateral miniscrews for anchorage, to contain the excessive proclination of lower incisors. At the end of treatment, the patient maintained the convex profile with the malocclusion correction by dentoalveolar compensation, achieving a satisfactory control of the inclination of lower incisors. Thus, it may be concluded that using this appliance associated with miniscrews for anchorage allows a conservative approach in Class II treatments.